FREQUENCY OF DEPRESSION AND ANXIETY AMONGADULT EPILEPTIC PATIENTS - Monica Vaswani (Baqai Journal of Health Sciences)
Epilepsy is a common neurological disease that greatly affects quality of life. Although not cured but easily managed by anti-epileptic medications, it is known to be associated with many other psychiatric co-morbid conditions including depression and anxiety. These psychiatric morbidities are often overlooked thus complicating the disease prognosis. The object of this study was to determine the frequency of depression and anxiety among adult epileptic patients. This study has been conducted in the Outpatient Department of Neurology, Dr Ruth K. M. Pfau Civil Hospital Karachi, Pakistan during November 20, 2016 to May 28, 2017. A total of 171 patients were enrolled during this period. Hamilton rating scale for depression (HRSD) and Hamilton anxiety rating scale (HAM-A) were used for assessment and the data was analyzed statistically. Among 171 patients, mean age was found to be 38.05±6.42 years with majority of the patients were female i.e. 103 (60.2%). Depression has been noted in 105 (61.4%) patients with majority cases having moderate severity 47 (44.7%). On the other hand, anxiety has been diagnosed in almost all selected patients. Similar to depression, it has also been found to be of moderate severity i.e. 83/171 (48.5%). In a stigmatized society like Pakistan, living with epilepsy is a problem. It is further aggravated by having associated psychiatric co-morbid conditions. This study revealed a high prevalence of depression and anxiety among epileptic patients living in Pakistan. Therefore, it is suggested that epileptic patients may also be investigated and treated for such co-morbid conditions for better clinical outcome.